2018
DOI: 10.22226/2410-3535-2018-2-174-177
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of folding during the superplastic forming of corrugated core panels

Abstract: Corrugated core panels manufactured by methods of superplastic forming concurrent with diffusion bonding (SPF / DB) are promising for the production of high specific strength articles. One of serious problems arising in forming of corrugated core panels is concerned with the formation of outer folds. The cause of folding is uneven deformation of the skin sheets. In this study, the process of forming a corrugated core panel from a titanium alloy VT6 (analogue of Ti-6Al-4V) by computer simulation is considered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In [18] it is shown that at an inclination angle of 35°, the formation of folds can be avoided by choosing the mode of holding the structure under pressure. The purpose of the present study is to determine the degree of influence of the angle of inclination of the stiffeners of the corrugated structure on folding.…”
Section: Introductionmentioning
confidence: 99%
“…In [18] it is shown that at an inclination angle of 35°, the formation of folds can be avoided by choosing the mode of holding the structure under pressure. The purpose of the present study is to determine the degree of influence of the angle of inclination of the stiffeners of the corrugated structure on folding.…”
Section: Introductionmentioning
confidence: 99%